Information Technologies for Development of Specific Regions of Poland in Assessment of the Analytic Hierarchy Process Method - Stanisław Ceran (Barometr Regionalny, 2015)
The article presents the role of information technologies in the process of development of the economically weak regions of Poland. The state and the dynamics of the process of information technologies, in relation with the digitization, mobility and cloud computing processing trends in the areas of public administration and economics as well as functioning of individual households show vast diversification in those areas. The aim is formulating an answer to the question concerning the efficiency of the solutions being introduced in the area of public administration and the level of the IT implementation within the range of the basic economic activities, as well as the services provided to the inhabitants. The state of completion of the regional programs, the national strategies for IT implementation, the Digital Agenda for Europe as well as infrastructural investments are subject to assessment with use of the Analytic Hierarchy Process method. An important part of the process is the factor of user willingness to adopt the technologies, skills and competences necessary for their effective use and that problem was assessed with utilization of the comparison method.